Peranan Pemerintah dalam Pengelolaan Pariwisata Menurut Undang-undang Nomor 10 Tahun 2009 - Sukarno, Sukarno (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2016)
Tourism in the era of regional autonomy is the realization of the ideals of the nation of Indonesia to promote common kesejahteraan and participate in implementing world order based on freedom, lasting peace and social justice.